FEED EFFICIENCY VERSUS SURVIVAL RATE: DETERMINANTS OF PRODUCTIVITY IN SANGKURIANG CATFISH (Clarias gariepinus) CULTURED UNDER TROPICAL AQUACULTURE SYSTEMS IN LAMPUNG PROVINCE, INDONESIA - Adimas Bagus Fahturohman; Wijayanti Ristyaningrum; Stella Feska; Zakyatul Muna; Farid Mukhtar Riyadi (Universitas Mataram, 2026)
Feed efficiency and survival rate are two key parameters determining the success and productivity of Sangkuriang catfish (Clarias gariepinus) aquaculture, particularly under intensive tropical culture systems. This study aimed to quantitatively analyze the relationship between feed efficiency and survival rate in determining the productivity of Sangkuriang catfish cultured in Lampung Province, Indonesia. The study was conducted over one production cycle using a completely randomized design with three different feed treatments (Feed A, B, and C), without specifying commercial brands, and using eight replicates. Observed parameters included feed conversion ratio (FCR), survival rate (SR), and biomass productivity. Data were analyzed using the Kruskal–Wallis test, correlation analysis, and multiple linear regression. The results showed that differences in feed formulation significantly affected feed efficiency, as indicated by variations in FCR. Still, they did not result in significant differences in survival rate or final productivity. Correlation analysis revealed a significant positive relationship between survival rate and productivity, while FCR showed a negative but statistically insignificant relationship with productivity. Regression analysis further confirmed that the survival rate was the dominant predictor of productivity, whereas feed efficiency primarily functioned as a factor optimizing resource utilization. This study concludes that under tropical aquaculture systems with low and stable mortality, productivity is more strongly determined by population stability than by variations in feed efficiency alone. These findings contribute to the understanding of productivity determinants in tropical catfish farming and provide practical insights for feed formulation strategies and aquaculture management aimed at improving efficiency and sustainability.